The thief Lord - Funke, Cornelia Caroline (Scholastic, 2002)
Escaping the aunt who wants to adopt only one of them, two orphaned brothers run away from Hamburg to Venice, finding shelter with a gang of street children and their leader, the thirteen-year-old "Thief Lord," while also eluding the detective hired to return them to Germany.